Simultaneous detection of fetal aneuploidy, de novoFGFR3 mutations and paternally derived β‐thalassemia by a novel method of noninvasive prenatal testing. (21st January 2021) - Yang, Lin; Wu, Yujing; Hu, Zhiyang; Zhang, Haiping; Pu, Dandan; Yan, Huijuan; Zhang, Sijia; Jiang, Hui; Liu, Qiang; Yuan, Yuying; Zhang, Yanyan; Chen, Fang; et al.
Abstract: Objective: The aim is to develop a novel noninvasive prenatal testing (NIPT) method that simultaneously performs fetal aneuploidy screening and the detection of de novo and paternally derived mutations. Methods: A total of 68 pregnancies, including 26 normal pregnancies, 7 cases with fetal aneuploidies, 7 cases with fetal achondroplasia or thanatophoric dysplasia, 18 cases with fetal skeletal abnormalities, and 10 cases with β ‐thalassemia high risk were recruited. Plasma cell‐free DNA was amplified by Targeted And Genome‐wide simultaneous sequencing (TAGs‐seq) to generate around 99% of total reads covering the whole‐genome region and around 1% covering the target genes. The reads on the whole‐genome region were analyzed for fetal aneuploidy using a binary hypothesis T‐score and the reads on target genes were analyzed for point mutations by calculating the minor allelic frequency of loci on FGFR3 and HBB . TAGs‐seq results were compared with conventional NIPT and diagnostic results. Results: In each sample, TAGs‐seq generated 44.7–54 million sequencing reads covering the whole‐genome region of 0.1–3× and the target genes of >1000×depth. All cases of fetal aneuploidy and de novo mutations of achondroplasia/thanatophoric dysplasia were identified with high sensitivities and specificities except for one false‐negative paternal mutation of β‐ thalassemia. Conclusions: TAGs‐seq is a novel NIPT method that combines the fetal aneuploidy screening and the detection of de novo FGFR3 mutations and paternal HBB mutations. Key Points: What's already known about this topic? Recently, the improvement of noninvasive prenatal testing (NIPT) allowed the expanded detection of chromosomal copy number variants (CNVs) and monogenic diseases in fetus. However, the expanded detection of CNVs and monogenic disease usually requires separate experiment procedures such as quantitative polymerase chain reaction (qPCR), digital PCR or haplotype‐assisted approaches, which could not be integrated with the screening of chromosome aneuploidy and lack of laboratory efficiency What does this study add? We developed a novel NIPT method that could simultaneously detect fetal aneuploidies, autosomal dominant diseases, and the paternally inherited mutations of autosomal recessive diseases without additional experiments. We validated this method using the plasma samples of pregnant women carrying fetal achondroplasia, thanatophoric dysplasia, and β ‐thalassemia, which showed promising results